2016
DOI: 10.1186/s13256-016-1135-9
|View full text |Cite
|
Sign up to set email alerts
|

Possible failure of novel direct-acting oral anticoagulants in management of pulmonary embolism: a case report

Abstract: BackgroundThe relative effectiveness of vitamin K antagonists compared with novel oral anticoagulants in treating pulmonary embolism remains unclear. Recent trials comparing the efficacy of vitamin K antagonists with factor Xa inhibitors for the treatment of pulmonary emboli have been non-inferiority studies based primarily on risk reduction (such as bleeding events), rather than resolution of specific diseases such as pulmonary embolism. Consequently, there is a lack of evidence indicating which of these agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In addition, carbamazepine, phenobarbital, phenytoin, and valproic acid have been shown to be able to induce both CYP3A4 and P-GP, although the effect varies in different models (11)(12)(13)(14)(15)(16)(17)(18). Critical DDIs may be associated with failure of the anticoagulation effect and expose the patients to the risk of recurrent stroke and systemic embolism (19,20). On the other hand, switching ASMs to avoid DDIs has been associated with a 16.7-21.7% increased risk in 6-month seizure recurrence rate (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, carbamazepine, phenobarbital, phenytoin, and valproic acid have been shown to be able to induce both CYP3A4 and P-GP, although the effect varies in different models (11)(12)(13)(14)(15)(16)(17)(18). Critical DDIs may be associated with failure of the anticoagulation effect and expose the patients to the risk of recurrent stroke and systemic embolism (19,20). On the other hand, switching ASMs to avoid DDIs has been associated with a 16.7-21.7% increased risk in 6-month seizure recurrence rate (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…The recent addition of factor Xa inhibitors to anticoagulant agents is not without fault (i.e., failure, bleeding, and lack of reversal agents), as demonstrated in this case report and other papers [6, 7, 12]. The risk factors for failure of anticoagulation therapy are vast and vary from patient to patient; pharmacodynamics, pharmacokinetics, metabolism, and elimination all have a hand in how a drug interacts in a given patient and are further discussed below [1315].…”
Section: Discussionmentioning
confidence: 53%
“…A thorough literature review revealed little in the way of reports of rivaroxaban failure in the treatment of DVT, although a few case reports in which potential rivaroxaban failure is noted have emerged recently [6, 7]. Postmarketing surveillance is clearly an important factor in the further development, safety, and efficacy of any novel drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment failure of thromboembolism was previously mentioned in the literature, with an incidence rate of 2% [ 12 - 13 ]. One case report published in 2016, of a patient treated with different classes of DOACs, failed to resolve pulmonary clots who needed final treatment with warfarin [ 14 ]. Another case was reported in 2017 with recurrence of DVT while on apixaban.…”
Section: Discussionmentioning
confidence: 99%